Approach to livelihood in desert area of Rajasthan through cattle development - BHAGAT, R L; GOKHALE, S B; CHOURASIA, A K (The Indian Journal of Animal Sciences, 2012)
An area of 5 Cattle Development Centres (CDC) covering 1690 beneficiaries in Parbatsar, Riyabadi and Mertacity tahsils of Nagour district of Rajasthan were selected to undertake the project from 2008–2011. The project activities involved artificial insemination at the door step of farmers using frozen semen of Tharparkar breed bulls, establishing demonstration of silvi-pasture on community land, training programme for cattle owners regarding improved animal management practices and monitoring progeny growth for impact assessment. To demonstrate the concept of silvipasture a model of 1ha was developed and available fodder sold on auction basis and animal owners appreciated the efforts. Basline survey results indicated that 33.49% animals were non descript and 0.17% population had Tharparkar breeds. These animals were targeted to produce improved progeny by breeding through use of semen from Tharparkar breed bulls (dam’s milk yield 2600 to 2975 kg) which were selected and procured from Central Cattle Breeding Farm, Suratgarh (Ganganagar). Average body weight at 3 months was 46.96±1.49 kg and 43.51±0.88 kg for males and females, respectively. Body weight at 6–, 9 -, 12 -, 15 - and 18-months was 81.64±7.37, 102.02±8.37, 111.23±7.52, 136.99±11.35, 155.11±15.07 kg, respectively, for males and 73.06±3.98, 94.02±7.47, 100.03±4.36, 121.94±5.86, 149.59±5.60 kg, respectively for females. The female progenies got pregnant during this project period at 20 months and another at 21 months of her age. These achievements could be attributed to the efforts of farmers and project staff through training and personal visits to door step.